Dissipation of dimethoate and fenitrothion in yard long bean and tomato under supervised field trials (Asian-Australasian Journal of Food Safety and Security, 2022)
The study was conducted to detect and quantify the residue of dimethoate and fenitrothion in yard long bean and tomato depending on the maximum residue limit (MRL) set by European Union. Four supervised field trials were conducted and sprayed with the recommended dose (2 ml/L of water) of dimethoate and fenitrothion. Samples were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 and 11days after spray (DAS). The collected samples were analyzed using Gas Chromatography (GC) coupled with Electron Capture Detector (ECD). The residue of fenitrothion was detected up to 8 DAS in tomato and 9 DAS in yard long bean and the levels of residues were 8.983-0.076 mg/kg in tomato and 6.187- 0.056 mg/kg in yard long bean which were above MRL. No residue was detected at 9 DAS in tomato and 10 DAS in yard long bean. The residue of dimethoate was detected up to 9 DAS in tomato and 10 DAS in yard long bean. The quantities of residues were decreased gradually over time and these were 6.521- 0.034 mg/kg in tomato and 8.590-0.046 mg/kg in yard long bean which were above MRL. No residues were detected at 10 DAS in tomato and 11 DAS in yard long bean.Asian Australas. J. Food Saf. Secur. 2022, 6 (1), 27-34